The Effect of the GeoGebra-Assisted Problem-Based Learning Model on Mathematical Creative Thinking Ability - Abbas, Nurhayati; Katili, St. Nur Qamariah; Machmud, Tedy (Technium Social Sciences Journal, 2025)
This research aims to examine the effectiveness of the GeoGebra-assisted Problem-Based Learning model on mathematical creative thinking abilities, considering initial mathematics ability. The study employed a quasi-experimental design using a 2x2 treatment level with two-way analysis and the Tukey test. The research was conducted in Class VIII of SMP Negeri 1 Kabila during the even semester of the 2023-2024 academic year. Data were collected through a descriptive mathematical creative thinking ability test and a multiple-choice initial mathematics ability test. The analysis of the mathematical creative thinking ability data was based on categorizing the initial mathematics ability test scores, which served as a moderator variable, distinguishing between high and low initial mathematics abilities. Data analysis utilized two-way analysis of variance to test the research hypotheses. The results of this study indicate that: (1) Students’ mathematical creative thinking abilities taught using the GeoGebra-assisted Problem-Based Learning model are higher compared to those taught with conventional learning models; (2) There is an interaction effect between the learning model and initial mathematics ability on students’ mathematical creative thinking abilities; (3) Students with high initial mathematics ability taught using the GeoGebra-assisted Problem-Based Learning model demonstrate higher mathematical creative thinking abilities than those taught with conventional learning models; (4) Students with low initial mathematics abilities taught using the GeoGebra-assisted Problem-Based Learning model exhibit lower mathematical creative thinking abilities than those taught using conventional learning models.